Association between acne and anxiety in adolescents and young adults: A systematic review of observational studies (Research, Society and Development, 2025)
Acne is a prevalent dermatological condition among adolescents and young adults, with a multifactorial etiology and high prevalence. Beyond its physical impacts, recent studies have demonstrated a strong association between acne and emotional manifestations, especially anxiety symptoms, which can impair self-esteem, quality of life, and social relationships. This study conducted a systematic literature review, following PRISMA guidelines, aiming to analyze the association between acne and anxiety in adolescents and young adults. The findings showed that individuals with acne are at higher risk of developing anxiety symptoms compared to control groups. Psychosocial factors, such as social stigma and body image perception, were identified as relevant contributors to the intensity of psychological distress. It is concluded that acne management should include not only dermatological interventions but also psychological support, ensuring a comprehensive and multidisciplinary approach.